2010
DOI: 10.1037/a0018875
|View full text |Cite
|
Sign up to set email alerts
|

Lipid trajectories as predictors of depressive symptoms: The Young Finns Study.

Abstract: Objective The aim of this study was to identify common trajectories of lipid levels across childhood and early adulthood life span. Design The sample was a subpopulation of 824 young adults (3 – 9 years at baseline in 1980) of the on-going population-based prospective Cardiovascular Risk in Young Finns Study. Lipid levels were determined in 1980, 1983, 1986 and 2001. Main outcome measures Depressive symptoms were assessed using a modified version of Beck’s Depression Inventory in 1992 and 2001. Results T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 53 publications
1
46
0
Order By: Relevance
“…Antiinflammatory treatment that inhibits IL-6 also inhibits triglycerides [55]. Elevated IL-6 [9] and triglycerides [56] levels in childhood are associated with increased risk of depression in young adulthood. However, lowering of serum cholesterol in middle-aged subjects by diet, drugs, or both, leads to a decrease in CHD but an increase in deaths due to suicide or violence [57].…”
Section: Discussionmentioning
confidence: 99%
“…Antiinflammatory treatment that inhibits IL-6 also inhibits triglycerides [55]. Elevated IL-6 [9] and triglycerides [56] levels in childhood are associated with increased risk of depression in young adulthood. However, lowering of serum cholesterol in middle-aged subjects by diet, drugs, or both, leads to a decrease in CHD but an increase in deaths due to suicide or violence [57].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory treatment that inhibits IL-6 also inhibits triglycerides 51 . Elevated IL-6 9 and triglycerides 52 levels in childhood are associated with increased risk of depression in young adulthood. However, lowering of serum cholesterol in middle-aged subjects by diet, drugs, or both, leads to a decrease in CHD but an increase in deaths due to suicide or violence 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported raised TG in depression(e.g. [42][43][44][45] ), but meta-analysis on the topic is lacking. Of note, a prospective study in Finnish young adults showed that steeply rising TG levels throughout childhood and adulthood was associated with increased DS in adulthood 43 , consistent with the present finding of a causal role of TG in the development of DS.…”
Section: Discussionmentioning
confidence: 99%